The microfluidic artificial lung: Mimicking nature's blood path design to solve the biocompatibility paradox. Issue 7 (6th May 2022) - Astor, Todd L.; Borenstein, Jeffrey T.
Abstract: The increasing prevalence of chronic lung disease worldwide, combined with the emergence of multiple pandemics arising from respiratory viruses over the past century, highlights the need for safer and efficacious means for providing artificial lung support. Mechanical ventilation is currently used for the vast majority of patients suffering from acute and chronic lung failure, but risks further injury or infection to the patient's already compromised lung function. Extracorporeal membrane oxygenation (ECMO) has emerged as a means of providing direct gas exchange with the blood, but limited access to the technology and the complexity of the blood circuit have prevented the broader expansion of its use. A promising avenue toward simplifying and minimizing complications arising from the blood circuit, microfluidics‐based artificial organ support, has emerged over the past decade as an opportunity to overcome many of the fundamental limitations of the current standard for ECMO cartridges, hollow fiber membrane oxygenators. The power of microfluidics technology for this application stems from its ability to recapitulate key aspects of physiological microcirculation, including the small dimensions of blood vessel structures and gas transfer membranes. An even greater advantage of microfluidics, the ability to configure blood flow patterns that mimic the smooth, branching nature of vascular networks, holds the potential to reduce the incidence of clotting and bleeding and to minimize reliance on anticoagulants. Here, we summarize recent progress and address future directions and goals for this potentially transformative approach to artificial lung support. Abstract : Correspondence between native blood vessel branching and the microfluidic blood vessel branching patterns that form the design basis for bio‐inspired artificial organs. As in the physiological vasculature, a large inlet vessel branches into multiple trunk lines, each of which leads to further branching into smaller microchannels. This design paradigm preserves a smooth distribution of blood flow throughout the microfluidic network.